Factors Affecting Accountability Government Institution Performance - Arthur Simanjuntak; Septony B. Siahaan; Duma Rahel Situmorang; Duma Megaria Elisabeth (Universitas Negeri Semarang, 2023)
Purpose : The purpose of this empirical study is to investigate the influence of internal control, clarity of budget targets, reporting systems, and performance-based regional budgets on the performance accountability of government agencies within the Regional Financial and Asset Management Agency of the North Sumatra Provincial Government. Method : This study employs a causative contextual research approach. The population for this study consists of 119 individuals. Primary data for this research were collected using an empirical approach, which involved the distribution of questionnaires to respondents. One hundred-five questionnaires were sampled and analyzed through the saturated sampling method. Findings : The results indicate that both simultaneous and partial effects of internal control, clarity of budget targets, reporting systems, and performance-based budgets significantly influence the performance accountability of government agencies within the Regional Financial and Asset Management Agency of the North Sumatra Provincial Government. Novelty : This research distinguishes itself from previous studies by highlighting that the variable with the most substantial impact on the performance accountability of government agencies within the BPKAD of the North Sumatra Provincial Government is a combination of internal control, clarity of budget targets, reporting systems, and performance-based regional budgets, which form an inseparable unit. Keywords : Internal Control; Clarity of Budget Goals, Reporting System; Performance-Based Budget; Performance Accountability of Government Agencies